Impact of Training on Expectation of Employee and Employer: A comparative study - Javed, Syed Muhammad; ., Saqib Muneer; ., Melati Ahmad Anuar (Information Management and Business Review, 2013)
Organizations today spend millions of dollars on training to enhance the performance of their employees, which leads to formation of expectation on employers end as well as employees ends observing this phenomena ,this research was conducted to analyze the expectations of employee and employer and its impact on post training satisfaction, for that matter data was collected from 20 organization where training is provided ,sample size was 20 training / HR managers and per managers 5 employees, paired sample t test was applied to gauge the difference or similarity between the perception and expectation of employees and employer, after the analysis it was found that there is significant difference between the perception of employee and employers on the expected training outcomes and no similarity existed between the expectation of employee and employer which did not have positive effect on post training satisfaction.